2020
DOI: 10.21203/rs.2.17010/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to primary healthcare services and associated factors in urban slums in Nairobi-Kenya

Abstract: Background: Access to primary healthcare is crucial for the delivery of Kenya’s universal health coverage policy. However, disparities in healthcare have proved to be the biggest challenge for implementing primary care in poor-urban resource settings. In this study, we assessed the level of access to primary healthcare services and associated factors in urban slums in Nairobi-Kenya. Methods: The data were drawn from the Lown scholars’ study of 300 randomly selected households in Viwandani slums (Nairobi, Kenya… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Therefore, they preferred not to refer for treatment or to postpone it as much as possible. Because, affordability is effective in receiving treatment [34]. Some participants in our study stated that some services were provided only in certain areas and people had to travel to access these services; consequently, inaccessibility caused some people to avoid seeing a doctor or to delay it as much as possible.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, they preferred not to refer for treatment or to postpone it as much as possible. Because, affordability is effective in receiving treatment [34]. Some participants in our study stated that some services were provided only in certain areas and people had to travel to access these services; consequently, inaccessibility caused some people to avoid seeing a doctor or to delay it as much as possible.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, they preferred not to refer for treatment or to postpone it as much as possible. Because, affordability is effective in receiving treatment (34). A number of participants of our study stated that some services were provided only in certain areas and people had to travel to access these services; consequently, inaccessibility caused some people to avoid seeing a doctor or to delay it as much as possible.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, lower economic status and lack of medical insurance were related to delaying treatment seeking for urinary incontinence (41). In general, affordability is effective in receiving treatment (42). One study found that the quality of care as well as the costs in uenced the participants' choices.…”
Section: Discussionmentioning
confidence: 99%